2018
DOI: 10.1002/mp.13199
|View full text |Cite
|
Sign up to set email alerts
|

CT sinogram‐consistency learning for metal‐induced beam hardening correction

Abstract: Purpose This paper proposes a sinogram‐consistency learning method to deal with beam hardening‐related artifacts in polychromatic computerized tomography (CT). The presence of highly attenuating materials in the scan field causes an inconsistent sinogram that does not match the range space of the Radon transform. When the mismatched data are entered into the range space during CT reconstruction, streaking and shading artifacts are generated owing to the inherent nature of the inverse Radon transform Methods Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 23 publications
0
74
0
Order By: Relevance
“…The average mean squared error between the required residual projection images and the estimated images from included artifact projection (with noise) image input can be implemented as the loss function q to learn the trainable parameters δ (SGDM with the weight decay of 0.0001, momentum of 0.9, initial learning rate of 0.1, and hyper-parameters mini-batch size and epochs) in the DnCNN [19]. With regard to δ , mini-batch size and epochs are hyper-parameters that affect MAR [23, 24]. We evaluated the optimal parameter, and we have applied the parameters in the “Evaluation” section below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average mean squared error between the required residual projection images and the estimated images from included artifact projection (with noise) image input can be implemented as the loss function q to learn the trainable parameters δ (SGDM with the weight decay of 0.0001, momentum of 0.9, initial learning rate of 0.1, and hyper-parameters mini-batch size and epochs) in the DnCNN [19]. With regard to δ , mini-batch size and epochs are hyper-parameters that affect MAR [23, 24]. We evaluated the optimal parameter, and we have applied the parameters in the “Evaluation” section below.…”
Section: Methodsmentioning
confidence: 99%
“…Deep learning approaches have successfully been employed recently, in pattern recognition and image processing methods, including image denoising [19], image super-resolution [20], and low-dose CT reconstruction [21, 22]. For instance, a convolutional neural network (CNN) has been implemented for artifact reduction in medical imaging [23, 24], and the CNN has been employed to get rid-off the residual errors from MAR. Even though these previous studies showed that the CNN could enhance MAR effectively, no study has been conducted on MAR using DT.…”
Section: Introductionmentioning
confidence: 99%
“…The current DL‐based MAR methods mainly seek to patch metal trace in corrupted sinograms, and then use filtered back‐projection (FBP) 24,25 to reconstruct the patched sinograms to CT images. For example, Ghani et al 26 used a ten‐layer fully convolutional network (FCN) 27 to patch metal trace; Park et al 28 used a U‐Net 29 like network to reduce metal artifacts; Zhang et al 30 proposed a multistep convolutional neural network (MSCNN) for MAR, and used an FCN to patch metal trace followed by a postprocessing step to suppress secondary artifacts; Lin et al 31 applied a U‐Net–like network to patch metal trace and employed the network for metal trace inpainting to reduce secondary artifacts. These DL‐based metal trace inpainting methods aimed to reduce more artifacts and incur less secondary artifacts than traditional sinogram restoration methods due to their better detail recovering capability.…”
Section: Introductionmentioning
confidence: 99%
“…Gjesteby et al [17] applied a combination of deep learning and normalized metal artifact reduction (NMAR) on a reconstructed image to correct the region with serious artifacts. Park et al [18] used U-Net to correct an inconsistent sinogram and eliminate beam-hardening factors triggered by main metals along the metal trace in a sinogram. Zhang et al [19] proposed an open MAR framework called CNN-MAR based on the deep learning model to reduce metal artifacts in CT images.…”
Section: Introductionmentioning
confidence: 99%